The Effect of Human Resources Quality and Religiusity on Employee Performance and Motivation as Moderating Variables - Gani, Nuraeni; Yusuf, Nina Anggereni (Adpebi International Journal of Multidisciplinary Sciences, 2022)
This study aims to examine how much influence the quality of human resources and religiosity on employee performance and motivation as moderating variables. This research uses quantitative research using associative approach. The number of samples used in this study were 24 respondents from employees using the saturated sampling method. This study uses a questionnaire that is measured using a Likert scale and the data analysis used is multiple linear regression analysis and moderate regression analysis using the SPSS 25 program application. The results of this study indicate that the quality of human resources has a positive and significant effect on employee performance, religiosity has an effect positive and significant impact on employee performance, the quality of human resources and religiosity have a simultaneous effect on employee performance, motivation is able to moderate the relationship between the quality of human resources on employee performance, and motivation is able to moderate the relationship between religiosity on employee performance at Bank Sulselbar Syariah Sengkang Branch.